Analysis of Molecular Stability on Waste Extracts of Trigona spp. Bees Haves. Ethanolically - Asfar, Andi Muhamad Iqbal Akbar; Asfar, Andi Muhammad Irfan Taufan (Universitas Negeri Semarang, 2021)
One of the local honey of South Sulawesi is Trigona honey which comes from Trigona spp. There are three types of trigona bees in South Sulawesi with each colony consisting of 300-80,000 individuals. Trigona bees are found nesting in hollow places such as logs, tree holes, and cracks in the walls of houses. The nest entrance is made of plant resin mixed with soil and mud, with different shapes and colors depending on the species. This type of bee produces a lot of propolis compared to honey and the price of honey produced is much higher because it has a chemical content (health benefits) that is much better than ordinary honey from the Apis mellifera group. This study was designed by extracting in ethanolic process at a concentration of 70%. The choice of concentration was based on previous research with an extraction temperature of 60 °C. The treatment of this research is to vary the time, namely 10 minutes, 20 minutes, and 30 minutes as a setting for the extraction time. Each treatment will be carried out in duplicate. This shows that in the honeycomb waste Trigona spp. contains terpenoids which are classified as antioxidants. Therefore, beehive waste Trigona spp. potential to be used as a source of antioxidants. In addition, several compounds are also relatively large antibacterial and anti-microbial compounds contained in the waste of Trigona spp beehives. The optimum solvent used by comparing the percentage of abundance (abundance/relative) through the percentage of the area and molecular stability after fragmentation is through the ethanolic process using ethanol solvent with percent abundance at 218 m/z and 189 m/z with the largest compound contained is Methyl Commate A and Alpha-Amyrin